Airway Management for Massive Anterior Mediastinal Tumor Resection in an Infant: A Strategy Involving Spontaneous Breathing-Preserving Endotracheal Intubation under Intravenous Anesthesia - Hiromi Matsuda; Ei Ito; Akiko Katsuike; Hirotsugu Okamoto (Case Reports in Pediatrics)
Tracheal intubation under sedation in uncooperative infants is challenging. The case of a 4-month-old infant with a massive anterior mediastinal tumor and upper respiratory tract symptoms, for whom effective preoxygenation was provided with a high-flow nasal cannula (HFNC), allowing for safe tracheal intubation in combination with a supraglottic device and local anesthetic, is reported. With careful planning of anesthesia and creative problem solving, airway management for anterior mediastinal tumors can be performed safely with the selection of an appropriate airway device. This may be a good airway management strategy for infants with mediastinal tumors or who may be expected to have ventilation difficulties.